2022
DOI: 10.1186/s13195-022-01120-6
|View full text |Cite
|
Sign up to set email alerts
|

Research attitudes in families of individuals with Down syndrome: importance for clinical trials

Abstract: Background Individuals with Down syndrome (DS) are increasingly eligible for clinical trial intervention, particularly for the treatment or prevention of Alzheimer disease (AD). Yet, little is known about research attitudes that may contribute to decisions regarding clinical trial enrollment for people with DS, a gap which is addressed in the current study. Methods The Research Attitudes Questionnaire (RAQ) is a brief validated instrument that meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In item‐level analyses, DS decision‐makers were more favorably disposed toward “responsibility for helping others through volunteering for medical research.” In our previous study, favorable attitudes toward research participation were also noted. 13 In children with DS under the age of 18 years, 72% of their parents expressed willingness to participate in research, although only 36% had actually enrolled in a clinical trial. Barriers to research participation for people with DS have been reviewed and include benefit‐risk assessment, time commitment, access to results, and the “power distance” between the researchers and families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In item‐level analyses, DS decision‐makers were more favorably disposed toward “responsibility for helping others through volunteering for medical research.” In our previous study, favorable attitudes toward research participation were also noted. 13 In children with DS under the age of 18 years, 72% of their parents expressed willingness to participate in research, although only 36% had actually enrolled in a clinical trial. Barriers to research participation for people with DS have been reviewed and include benefit‐risk assessment, time commitment, access to results, and the “power distance” between the researchers and families.…”
Section: Discussionmentioning
confidence: 99%
“…RAQ scores have been previously shown to be associated with willingness to participate in research, compliance with study protocols, and study completion. 9 , 10 , 11 , 12 In a previous study, we showed the feasibility of using the RAQ in over 1000 family members for individuals with DS, 13 but we still do not understand how individual items on the RAQ compare to those in the general population. In the present report, we explored differences in RAQ scores between healthcare and research enrollment decision‐makers for individuals with DS and those from a more general population, both of which come from research‐friendly registries in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…A summary score, ranging from 7 to 35, was calculated and weighted against the number of missing RAQ responses for each participant, with higher scores representing more positive research attitudes. Previous studies have demonstrated a relationship between the RAQ score and willingness to participate in research, as well as the likelihood of completion of clinical trials [15][16][17]. (2).…”
Section: Discussionmentioning
confidence: 99%
“…A summary score, ranging from 7 to 35, was calculated and weighted against the number of missing RAQ responses for each participant, with higher scores representing more positive research attitudes. Previous studies have demonstrated a relationship between the RAQ score and willingness to participate in research, as well as the likelihood of completion of clinical trials [ 15 , 16 , 17 ]. Willingness to participate in research activities: Participants were asked about their interest in being notified about studies (yes/no) which investigate approved medication, investigational medicine, diet or lifestyle alteration, blood draws, cognitive testing, magnetic resonance imaging (MRI), positron emission tomography (PET), lumbar puncture, autopsy, and on-site/at-home blood draws for genetic testing and biomarker quantification [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seven are examining intervention strategies for obstructive sleep apnea, three are addressing aging and AD risk, one is evaluating immune modulatory treatments for autoimmune skin A list of studies that are currently recruiting through the registry can be found on the DS-Connect website. Among the projects supported by the registry are a survey of dietary supplement use in children with DS (Lewanda et al, 2018), a survey of parents utilizing a validated tool to assess measures of global health in their children with DS (S. L. Santoro, Haugen, et al, 2023), application of the Research Attitudes Questionnaire to over 1000 families in the DS-Connect Registry (Lott et al, 2022), the comfort of caregivers with the transition to adult care for their children with DS (VanZant & McCormick, 2021), and a survey of preventive and gynecologic health care uptake by adult women with DS (Smith et al, 2020). One of the most significant events sponsored by the…”
Section: Ds Clinical Trialsmentioning
confidence: 99%